Spatio-temporal variability of some metal concentrations in the soil of eastern England, and implications for soil monitoring. - Lark, Murray R.; Bellamy, Patricia H.; Rawlins, Barry G. (Elsevier, 2006)
Previous workers have proposed the use of multivariate geostatistics for the problem of estimating temporal change in soil properties for soil monitoring, but this has yet to be evaluated. We present a case study of this approach from the Humber–Trent region in North East England. We extracted data from two sources on cobalt, nickel and vanadium concentrations in the topsoil on two dates. Auto-variograms were estimated for each metal on each date, and pseudo cross-variograms for each metal on the two dates. It was shown that robust estimators of the auto and pseudo cross-variograms were needed for the analysis of these data. A linear model of coregionalization was then fitted to describe the spatio-temporal variability of each metal.
Keywords: Geostatistics; Pseudo cross-variogram; Cokriging; Robust estimation; Soil monitoring; Heavy metals; Pedometrics